»V tistem trenutku smo začutili, da smo si blizu in da smo porušili mejo« - Devetak, Robert (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2025)
This article explores the contacts between Milojka Štrukelj Primary School in Nova Gorica and the lower secondary school in San Vendemiano, framing them as a form of regional cooperation between Slovenia and Italy. The partnership began in the 1960s, amidst bloc divisions and an unresolved national border between Italy and Yugoslavia. At the time, the legacies of fascism and the Second World War still deeply resonated on both sides. The article focuses on two key aspects of this collaboration: school holiday camps and the cultural exchange in 1972. Supported by local, regional, and national political institutions, the schools aimed to foster cross-border connections among young people, grounded in mutual respect and the overcoming of prejudice. This ambitious initiative also functioned as a form of cultural diplomacy between the two countries. Drawing on archival documents and press coverage, the article highlights the key features and lasting impact of these contacts, which helped shape the experiences of several generations of Slovene and Italian children.
Keywords: cultural diplomacy; cultural exchange; kulturna diplomacija; kulturna izmenjava; letovanja; Milojka Štrukelj Primary School; Nova Gorica; Osnovna šola Milojke Štrukelj; San Vendemiano; school holiday camps